A conformational-dependent interdomain redox relay at the core of protein disulfide isomerase activity - Pinho Melo, Eduardo (2024)
Protein disulfide isomerases (PDIs) are a family of molecular chaperones resident in the endoplasmic reticulum (ER) emerging as important factors in disease. In addition to an holdase function, some members catalyse disulfide bond formation and isomerization, a crucial step for native folding and prevention of aggregation of misfolded proteins. PDIs are characterized by a modular arrangement of thioredoxin-like domains, with the canonical, first identified PDIA1, organized as four thioredoxin-like domains forming a horseshoe with two active sites at the extremities. Using two fluorescent redox sensors, roGFP2 and HyPer, as client substrates either unfolded or native, and the in vitro reconstitution of the full pathways of oxidative protein in the ER, we clarified important aspects underlying the catalytic cycle of PDIA1. The N-terminal a active site is the main oxidant of thiols and can transfer electrons to the C-terminal a´ active site relying on the redox-dependent conformational flexibility of PDIA1 that allows the formation of an interdomain disulfide bond. The a´ active site act then as a crossing point to redirect electrons to the ER downstream oxidases or back to client proteins. The two active sites of PDIA1 work cooperatively as an interdomain redox relay that explains PDIA1 oxidative activity to form native disulfides and PDIA1 reductase activity to resolve scrambled disulfides. Moreover, this mechanism reveals a new rational for shutting perpetuity for this down oxidative protein folding under ER redox imbalance or when the levels of unfolded proteins and folding intermediates exceed the folding capacity of the system.